Effect of waxing with paraffin and modified atmosphere packaging on the storage of Cavendish Banana (Musa cavendishii L var. Montel) - Mustaffa, Razali; Osman, Azizah; Mohamed, Suhaila; Yusof, Salmah (Universiti Putra Malaysia Press, 2000)
Postharvest treatment with liquid paraffin, clingwrap, low density polyethylene (WPE) with and without potassium permanganate (KMnO) was studied to extend the shelf life of 'Montel' banana (Musa cavendishii L), under refrigeration (15±1 °C) and at ambient temperature (27±1 °C). The fruits packed in WPE with KMn04 ripened within 60 days after harvesting at week 12 from flower emergence. This was followed l7y treatments with clingwrap (42 days), liquid paraffin (36 days), control at 15±I°C (24 days) and control at ambient temperature (18 days). The percentage weight loss, peel and pulp colours of fruits increased significantly (P<O.OI) for all treatments during the storage period. On the other hand, the texture values and tannin content of the fruit decreased significantly (P<O.OI). The rise in total soluble solids (TSS) and sugar was slow initially but gradually increased at the end of the storage period. However, pH, titratable acidity (TA), ascorbic acid (AA) and starch contents o fruits from all treatments were found to be inconsistent during storage. There is a highly significant (P<O.OI) difference in the production of ethylene (CIl) and carbon dioxide (CO) found from fruits of all treatments during storage. Fruits packed in low density polyethylene (WPE) with KMn04 was found to be the best treatment to extend the storage life of 'Montel' banana.